(untitled) (Research, Society and Development, 2022)
The health crisis triggered by the COVID-19 pandemic has challenged public management in several countries to ensure the timely and efficient procurement of the various health technologies necessary to cope with it, such as medicines, diagnostic tests, personal protective equipment (PPE) and medical materials/equipment, among others. This article introduces a protocol for a scoping review that aims to map and synthesize studies portraying the management capacity related to public procurement of inputs used in coping with the crisis arising from COVID-19. The protocol is intended to document the processes involved in the methodological planning and execution of a scoping review guided by Joanna Briggs Institute guidelines and developed using the 2015 PRISMA-Protocols (PRISMA-P) checklist. The PCC strategy (population, concept and context) systematized the search for studies published in MEDLINE, LILACS, Scopus, Embase, Web of Science and WHO-COVID-19 (Global literature on coronavirus disease), as well as in the gray literature, by September 2021. The selection of articles will be carried out in two steps (titles and abstracts, followed by the assessment of the full text of the articles), by two independent reviewers, with the resolution of disagreements by a third reviewer. The results will be analyzed qualitatively/quantitatively and will be organized by themes. The checklist present in the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews (PRISMA-ScR) will be used to guide the final review report. The protocol was registered in the Open Science Framework under the number 10.17605/OSF.IO/W6KHY.